How does educational technology answer challenges? Empirical theoretical studies and public perspectives - Zahid Zufar At Thaariq; Ence Surahman (Intelektual Pustaka Media Utama, 2021)
Educational technology is part of a scientific that is mostly engaged in education. Actually, this scientific has significant benefits, especially in the field of education. However, many people do not understand the role of educational technology in education. This can be seen from the diverse perspectives of society on educational technology. When it is associated with educational technology science, there are many views of the community that are very opposite to the scientific clusters of educational technology taught from lectures. So, the purpose of this study was to find out the various perspectives of society regarding educational technology itself. This paper is presented with the addition of theoretical educational technology clumps. This research employed a descriptive qualitative approach. This study used indirect interviews, which means giving unstructured questions but still focusing on what will be researched. The subjects in this study were six participants who were people outside the educational technology scientific clump. In addition, the author also conducted a literature review which was taken from six articles from three different journals. The results of this study reveal a diverse picture of views on educational technology. All participants argue that educational technology has a significant role, but in terms of the dominant conception they still do not understand it like other scientific. From the results it can be a separate challenge for educational technology. It can be used as an alternative reference in improving the quality of educational technology, either through formal education or other forms.